21st century China : views from Australia - Farquhar, Mary Ann, 1949- (Cambridge Scholars, 2009)
Australia's Prime Minister Kevin Rudd famously said that China issues are part of 21st century Australia's 'very life-blood'. This brings short-term challenges to the Australia-China relationship, from Chinese investments in our resources to visits to Australia by expatriate regional political and religious leaders, labelled 'splittists' or 'terrorists', by the Chinese government. Our long-term relationship includes robust scholarship on China as an emerging superpower. In this book, leading ...